Outcomes of Liver Transplantation Among Older Recipients With Nonalcoholic Steatohepatitis in a Large Multicenter US Cohort: the Re‐Evaluating Age Limits in Transplantation Consortium. Issue 11 (13th October 2020) - Kwong, Allison J.; Devuni, Deepika; Wang, Connie; Boike, Justin; Jo, Jennifer; VanWagner, Lisa; Serper, Marina; Jones, Lauren; Sharma, Rajani; Verna, Elizabeth C.; Shor, Julia; German, Margarita N.; et al.
Abstract : The liver transplantation (LT) population is aging, with the need for transplant being driven by the growing prevalence of nonalcoholic steatohepatitis (NASH). Older LT recipients with NASH may be at an increased risk for adverse outcomes after LT. Our objective is to characterize outcomes in these recipients in a large multicenter cohort. All primary LT recipients ≥65 years from 2010 to 2016 at 13 centers in the Re‐Evaluating Age Limits in Transplantation (REALT) consortium were included. Of 1023 LT recipients, 226 (22.1%) were over 70 years old, and 207 (20.2%) had NASH. Compared with other LT recipients, NASH recipients were older (68.0 versus 67.3 years), more likely to be female (47.3% versus 32.8%), White (78.3% versus 68.0%), Hispanic (12.1% versus 9.2%), and had higher Model for End‐Stage Liver Disease–sodium (21 versus 18) at LT ( P < 0.05 for all). Specific cardiac risk factors including diabetes with or without chronic complications (69.6%), hypertension (66.3%), hyperlipidemia (46.3%), coronary artery disease (36.7%), and moderate‐to‐severe renal disease (44.4%) were highly prevalent among NASH LT recipients. Graft survival among NASH patients was 90.3% at 1 year and 82.4% at 3 years compared with 88.9% at 1 year and 80.4% at 3 years for non‐NASH patients (log‐rank P = 0.58 and P = 0.59, respectively). Within 1 year after LT, the incidence of graft rejection (17.4%), biliary strictures (20.9%), and solid organ cancers (4.9%) were comparable. Rates of cardiovascular (CV) complications, renal failure, and infection were also similar in both groups. We observed similar posttransplant morbidity and mortality outcomes for NASH and non‐NASH LT recipients. Certain CV risk factors were more prevalent in this population, although posttransplant outcomes within 1 year including CV events and renal failure were similar to non‐NASH LT recipients.